AKTIVITAS VULKANISME EKSPLOSIF PENGHASIL FORMASI SEMILIR BAGIAN BAWAH DI DAERAH JETIS IMOGIRI - Mulyaningsih, Sri; Husadani, Y T; Umboro, P A; Sanjoto, Siwi; Purnamawati, Dwi Indah (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2011)
The widely exposed of volcanic rocks within western part of Central Java-DIY Southern Mountain areas, indicates that volcanic activities had influenced geology of this area. Volcanic-stratigraphic study finds pumiceus rocks, tuff and co-ignimbrite breccias that can be described as primery volcanic rocks at study areas. Those volcanic rocks were erupted explosively followed by collapsing strato cone and forming new caldera. The associate of volcanic rocks with co-ignimbrite breccias, indicates that the central eruption was not far from the outcropes. Shallow intrusive rocks of andecites bearing hornblendes that exposed at the highest cone shape geomorphology of Gunung Gede, south to southwest Sudimoro, might be as the central eruptions.